Sediment transport in irrigation canals a new approach - Shende, Shivaji (SCITUS Academics LLC, 2016)
An irrigation canal is a waterway, often man-made or enhanced, built for the purpose of carrying water from a source such as a lake, river, or stream, to soil used for farming or landscaping. The engineering concept of efficiency at different levels of a canal system is important for planning, designing and even operating a canal irrigation system.